«È l'arte che conta non l'età». "Aging", divismo e protagonismo femminile in "Siamo donne" (Schermi. Storie e culture del cinema e dei media in Italia, 2021)
The film Siamo donne (We, the Women, 1953), written by Cesare Zavattini and divided into five episodes, represents an iconic case study to observe women of different ages and belonging to distinct generations. On the one hand, the first episode focuses on the ambitions of the young girls participating at the contest “Four stars and a starlet”; on the other hand, the following episodes, starring four celebrities playing the part of themselves, highlights the disillusions and regrets of mature women both in their private and professional life. Work, household, motherhood, and nostalgia are the main topics that interrelate with the portrayals of female aging provided by each episode. The film is a valuable opportunity to reflect upon the practices of cinema consumption and stardom in the 50s, especially from the contestants’ point of view. Throughout the analysis, we will also pay attention to voice over narration and the function of acousmatic voice as a memory device and expression of female subjectivity.